Pengaruh Modal Kerja, Jumlah Tujuan Negara, Jumlah Tenaga Kerja, Dan Kurs Dollar Amerika Terhadap Nilai Ekspor Kerajinan Bali Di Pasar Internasional - Ni Putu Intan, Permata Sari Ayu Indah; Marhaeni, A.A.I.N (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Foreign trade, especially exports very diverse handicrafts Bali is an important tool for economic growth to increase the consumption ability of a State. One of the things that can boost economic growth is international trade. Trade can boost economic growth (Salvatore, 2004: 358). The purpose of this study were: 1) to analyze the impact of working capital, the number of destination countries, the number of workers, and the US dollar exchange rate simultaneously on Bali handicraft export value in the international market., 2) to analyze the impact of working capital, the number of destination countries, the number of labor, and the US dollar exchange rate partially on Bali handicraft export value in the international market., 3) to analyze the variables dominant influence on Bali handicraft export value in the international market. This research was conducted in Denpasar by taking a sample of four exporters. The number of samples taken from four exporters during the last eleven years as many as 44 data points. Data collection is done by observation, interviews, and in-depth interviews. The analysis technique used is multiple linear regression. The analysis showed working capital, the number of destination countries, the number of workers, and the US dollar exchange rate have a significant effect simultaneously on Bali handicraft export value in the international market. Partially, working capital, the number of destination countries, the number of workers significant positive effect, while the US Dollar exchange rate, but no significant negative effect on the value of exports of handicraft Bali in the International market. Variables the dominant influence on Bali handicraft export value in the international market is the amount of labor.
Keywords: Working capital; the number of destination countries; the number of workers; the US dollar exchange rate; and the value of exports